2002
DOI: 10.1038/sj.bmt.1703654
|View full text |Cite
|
Sign up to set email alerts
|

Combination treatment of bullous pemphigoid with anti-CD20 and anti-CD25 antibodies in a patient with chronic graft-versus-host disease

Abstract: Summary:In this case report we describe a novel treatment with two chimeric monoclonal antibodies (MoAb) targeting the autoimmune B cell clone responsible for bullous pemphigoid (BP) as a manifestation of steroid refractory chronic graft-versus-host disease (GVHD) that developed after unrelated cord blood transplantation. Monitoring the BP-specific circulating antibodies and CD25-expressing activated T lymphocyte subset led us to combine anti-CD20 (Rituximab) mediated B cell ablation with anti-CD25 (Daclizumab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 8 publications
1
45
0
1
Order By: Relevance
“…The most commonly reported antibody-mediated immune diseases after HSCT are hypo-or hyperthyroidism, myasthenia gravis and immune cytopenias. 2 There are only a few case reports of antibody-mediated skin diseases after allogeneic HSCT, 1,3,4 and, to our knowledge, PF has never been reported after HSCT. Together with the recent report of bullous pemphigoid after cord blood transplantation, 1 this report shows that immune complications rarely or never reported after bone marrow transplantation may arise after cord blood transplantation.…”
mentioning
confidence: 99%
“…The most commonly reported antibody-mediated immune diseases after HSCT are hypo-or hyperthyroidism, myasthenia gravis and immune cytopenias. 2 There are only a few case reports of antibody-mediated skin diseases after allogeneic HSCT, 1,3,4 and, to our knowledge, PF has never been reported after HSCT. Together with the recent report of bullous pemphigoid after cord blood transplantation, 1 this report shows that immune complications rarely or never reported after bone marrow transplantation may arise after cord blood transplantation.…”
mentioning
confidence: 99%
“…68 Additionally, treatment with rituximab led to an incomplete response in a bullous pemphigoid-cGVHD patient. 69 But when adding daclizumab, an anti-CD25 antibody, a complete clinical response in combination with a complete decrease in bullous pemphigoid titer was observed. Daclizumab may have interrupted the helper function of CD4 + T cells, which facilitate the secretion of autoantibodies against bullous pemphigoid antigen 2 (BPAG2) by CD20-plasma cells.…”
Section: Co-ordinated B-and T-cell Responsementioning
confidence: 99%
“…For this purpose, a number of studies have analyzed the potential of rituximab in patients with cGVHD and have observed several positive effects, mostly including skin manifestations of cGVHD. 69,71,72,[86][87][88][89][90] A summary of all these studies is presented in Table 3. However, among many of the responding cGVHD patients, rituximab failed to establish a complete recovery.…”
Section: Treatment Of Cgvhd With Rituximabmentioning
confidence: 99%
See 2 more Smart Citations